Stock Network Stability After Crashes Based on Entropy Method - Yang, Ming-Yuan; Ren, Fei; Li, Sai-Ping (Frontiers in Physics, 2020)
This paper studies the stability of stock network after crashes based on the entropy method. By measuring the network stability using the entropy calculated with the degree distribution, we find that the entropy of stock network is close to the ER and WS networks. We further introduce the government rescue policies as a natural experiment and apply the measurement of entropy to study the influence of rescue polices after crashes on the network stability, and find that rescue policies only have short-term influence. Analysis of relation between stock degrees and government purchasing behaviors further verifies the influences of rescue policies on the stock network stability.